TDOF model for UHPC members under lateral low-velocity impact. (April 2023) - Jia, P C; Wu, H; Fang, Q; Peng, Q; Ma, L L
Highlights: Dynamic resistance functions for UHPC beams/columns are established and verified. A TDOF model is developed for the drop hammer impact test on UHPC beams/columns. TDOF model is verified based on the existing five series of drop hammer tests. The maximum and residual deflections of UHPC members under impact are formulated. Abstract: The dynamic behaviors of ultra-high performance concrete (UHPC) members under lateral low-velocity impact loading have been intensively studied by experiment and numerical simulation, while the corresponding structural design approach is still limited and mainly concerned in this study. Firstly, through comprehensively considering the compression arch action, strain rate effect, and unloading stiffness, the dynamic resistance function of UHPC members, e.g., reinforced UHPC (R-UHPC) and UHPC-filled steel tube (UHPC-FST) beams/columns, are built and verified. Then, a two degrees of freedom (TDOF) model of the drop hammer test on UHPC members is improved by considering the P - δ effect and stress wave propagation effect. Furthermore, the impact force- and mid-span deflection-time histories of the existing five series of drop hammer tests on UHPC members are applied to verify the validity and applicability of the established TDOF model. The influence of considering the stress wave propagation effect, strain rate effect, and steel fibers in UHPC for predictions of the TDOF model are discussed by parametric analyses. Finally, based on the energy balance, the explicit formulae are proposed to predict the maximum and residual mid-span deflections of the flexural critical UHPC members under the lateral low-velocity impact, which can be helpful for the design of UHPC structures under lateral impact loadings.